Object-oriented JavaScript: create scalable, reusable high-quality JavaScript applications, and libraries - Stefanov, Stoyan (From Technologies to Solutions, 2008)
The book requires no prior knowledge of JavaScript and works from the ground up to give you a thorough grounding in this powerful language. If you do already know some JavaScript, you will find plenty of eye-openers as you discover just what the language can do. This book takes a do-it-yourself approach when it comes to writing code, because the best way to really learn a programming language is by writing code. You are encouraged to type code into Firebug's console, see how it works and then tweak it and play around with it. There are practice questions at the end of each chapter to help review what you have learned.